A Model Driven Method to Represent Free Choice Petri Nets as Sequence Diagram - Thong , Weng Jie; M. A., Ameedeen (IEEE, 2015)
The role of modelling is important in software or system development. Modelling provides a way for developers to perform model design, model analysis and model synthesis. However, each phase have different requirements which leads to the use of different modelling language for each phase. For example, in model design, usually UML is used due to its semi-formal notational nature, making it easier for developers and other stakeholders without prior knowledge on modelling or programming language to understand. In model analysis, due to its mathematical needs in carrying out mathematical analysis, a modelling language with formal semantics like Petri Net is needed. This results in a condition called heterogeneity, where two modelling language could not communicate with each other. This paper aims to bridge the gap by introducing transformation rules between two type of modelling language which is Petri Net (from model analysis) and UML Sequence Diagram (from model design). This paper also aims to introduce a method of applying Model Driven Development (MDD) model transformation from Petri Nets to UML Sequence Diagram.